Neonatal Mesenchymal Hamartoma of Liver: An Unusual Presentation - Ramareddy, Raghu Sampally (Medknow Publications & Media Pvt Ltd, 2012)
Mesenchymal hamartoma of the liver is the second most common benign liver tumor in children. Typically, it presents as a large benign cystic, solid or mixed liver mass in a child younger than 3 years and amenable to complete resection. We report a neonate with Mesenchymal hamartoma of the liver presenting as giant intra abdominal cyst and its rare association with malrotation of bowel.